Multichannel Texture Segmentation Using Bamberger Pyramids. (30th September 2009) - Rosiles Rosiles, Jose Gerardo Jose Gerardo; Smith Smith, Mark J. T. Mark J. T.
Abstract : A multichannel texture segmentation algorithm is presented based on the image pyramids produced with the Bamberger directional filter bank. An extensive evaluation of Bamberger pyramids and their design parameters is presented. The impact on segmentation performance of factors like the number of pyramid levels, number of directional channels, redundancy and filter specifications is considered. The proposed system is shown to provide some of the best results reported to date when compared with other multichannel representations under similar evaluation conditions. It is further shown that segmentation results using the maximally decimated directional filter bank rival those of the undecimated case. To the knowledge of the authors, such performance has not been previously observed for decompositions with decimated channels.